A Bibliometric Analysis of Trends in Real-Time Coach Feedback Technologies in Sports - Sendi Cornelia; Dikdik Zafar Sidik; Agus Rusdiana; Mustika Fitri (Universitas Negeri Semarang, 2025)
This study explores the role of coach feedback in improving athlete performance through a bibliometric analysis approach. Coach feedback is proven to be crucial in enhancing skills, motivation, and the relationship between coaches and athletes. Using data from Scopus (2014–2024), this study maps publication trends, international collaborations, and dominant research themes related to coach feedback. The findings indicate that a combination of positive and corrective feedback is more effective, while context-based and interpersonal approaches enhance its effectiveness. Despite providing comprehensive insights, this study faces limitations in terms of language scope, database coverage, and a lack of in-depth qualitative analysis. This study serves as an important foundation for further research development on feedback in the sports domain.